The Scenario of the University of the Third Age Models for Lifelong Learning of the Thai Aging Groups - Ratana-Ubol, Archanya; Charungkaittikul, Suwithida; Sajjasophon, Ravee (Kasetsart Journal of Social Sciences, 2015)
This research is a qualitative research study, using future study technique. The purposes were to (1) analyze and synthesize the principles and concepts of the lifelong learning organization for the aging groups both in Thailand and foreign countries; (2) study various perspectives of the experts in the fields about the feasible scenario of the University of the Third Age models for lifelong learning of the Thai aging groups and strategic forming for the practical implementation; and (3) propose the scenario of the University of the Third Age models for lifelong learning of the Thai aging groups, as well as presenting the implementation strategies of the developed models. The analysis and synthesis’ results about concepts and implementation of the University of the Third Ages showed there were two main principles in organizing lifelong learning for the aging groups: formal University-based Model and flexible Self-Help Model involving the collaboration and participation from learning networks. The scenario of the University of the Third Age models for lifelong learning of the Thai aging groups comprised of four implementation models: short course programs, schools for seniors, informal learning activities, and visual classrooms (or vU3A). The University of the Third Age aims to provide learning activities for enhancing senior citizens in different lives’ dimensions. There were four implementation strategies, 1) to promote the lifelong learning activities for senior citizens in terms of university short course programs; 2) to promote the lifelong learning activities for senior citizens in terms of schools for seniors; 3) to promote the lifelong learning activities for senior citizens in terms of informal learning; and 4) to promote the lifelong learning activities for senior citizens in terms of visual classrooms or online-learning programs. Finally, the scenario of the University of the Third Age models for lifelong learning of the Thai aging groups was appropriate, effective, possible for the implementation; relevant to the contexts, useful and sustainable.